HTML-Based Interactive Crossword Puzzles for Science Learning Content in Elementary School - Saskara BG, I Wayan Tirta; Margunayasa, I Gede; Paramita, Made Vina Arie (Universitas Pendidikan Ganesha, 2024)
The less-than-optimal use of technology in implementing learning impacts learning media becoming less interactive and less varied. This research aims to develop HTML-based interactive crossword media, especially science content theme 6 subtheme 1 class V. This research includes a type of development using the ADDIE model, and its implementation is limited to the development stage only. The subject of this research is interactive crossword puzzle learning media. The data collection method and instrument used was a questionnaire. Quantitative and qualitative descriptive analysis is used as a data analysis technique. The research results show that the validity of interactive crossword puzzles by qualified material experts is very good. The results of the practicality of crossword puzzle media by teachers obtained practical criteria, individual students obtained practical criteria, and small groups of students obtained practical criteria. Thus, the novel learning media in the form of HTML-based interactive crossword puzzles on science content theme 6 subtheme 1 class V is feasible and practical. This research implies that it can be used as an interactive learning media option that utilizes technology in schools to improve and determine students' understanding of the material provided.